HUBUNGAN KECEMASAN DAN BEBAN KELUARGA DENGAN KEMAMPUAN ANGGOTA KELUARGA MERAWAT PASIEN PERILAKU KEKERASAN DI RUMAH SAKIT JIWA PROF. DR. SOEROJO MAGELANG - Indah Permatasari; Ririn Isma Sundari; Arni Nur Rahmawati (Jurnal Ilmu Keperawatan Komunitas, 2018)
The number of people with mental disorders in Central Java 2012 is quite high. It is about 3.300-9.300 people. This number is only from the diagnosed patients. One of them is mental disorder of violent behavior. The data obtained from RSJ Prof. Dr. Soerojo Magelang about this disorder reached 643 patients from May to October 2017. Violent behavior raises anxiety and burdens on families who care the people with violent behavior. The objective of this research was to find out the anxiety and family burden relationships with family members ability in caring violent behavior patients in RSJ Prof. Dr. Soerojo Magelang. This research used cross sectional approach with 52 total of samples. The technique used was purposive sampling, and the research instruments were anxiety questionnaire (HARS), family burden (ZBI), families’ ability in caring violent behaviour patients and also spearmen rank statictic test. Theresult shows that there is the anxiety is on average level which is 48,1%, the burden is also in average level which is 59,6% and the caring ability is not good which is 63,3%. There is a relationship of anxiety with the ability of family members to treat patients with violent behavior. And there is a family burden relationship with the ability of family members to care for patients of violent behavior.